Effect of Low Level Laser Therapy with Neuromuscular Training Program on Pain, Function and Muscle Strength in Participants with Knee Osteoarthritis: A Randomised Controlled Trial - D Thaheera; K Kotteeswaran; K Nishitha (Journal of Clinical and Diagnostic Research)
Introduction: The predominantly encountered progressive musculoskeletal condition that may negatively impact joints is Osteoarthritis (OA), which often affects the joints of the lower extremities since they support more than half of the body weight. By 2020, OA was predicted to increase by almost 40% in prevalence, ranking as the fourth most prevalent cause of disability globally. Aim: To compare the effect of Low Level Laser Therapy (LLLT) with a neuromuscular training programme and an aerobic exercise programme on pain, function, and muscle strength in participants with knee OA. Materials and Methods: A randomised, double-blind study was carried out at Saveetha Medical College and Hospital, Chennai, Tamil Nadu, India, from 26 October 2024 to 20 January 2025, involving 36 participants aged 50-65 years, diagnosed with unilateral OA of the knee (Kellgren-Lawrence grade II/III) based on American College of Rheumatology criteria. Participants were randomly assigned to the neuromuscular training programme group (age: 60.27±3.05 years, Body Mass Index (BMI): 24.285±0.50) or the aerobic exercise programme group (age: 61.055±2.7 years, BMI: 23.88±0.52) using a simple random sampling technique (lottery method). Outcome measures included the pressure algometer, Timed Up and Go (TUG) test, and 30-second sit-to-stand test. Pre and post-tests were conducted before and after eight weeks of intervention. Statistical analysis was performed using independent t-tests, both paired and unpaired, with a significance level of p<0.0001. Results: The post-test mean±SD values using the pressure algometer for the LLLT with the neuromuscular training group were 8.433±0.594, while for the LLLT with the aerobic exercise programme group, they were 6.661±0.566. The post-test mean±SD values using the 30 seconds sit to stand test for the LLLT with the neuromuscular training group were 18.67±1.24, but for the LLLT with the aerobic exercise programme group, they were 12.83±1.38. The post-test mean±SD values using the TUG test for the LLLT with the neuromuscular training group were 10.44±1.76, while for the LLLT with the aerobic exercise program group were 16.28±1.84. Conclusion: This study concludes that the neuromuscular training programme showed a promising effect in reducing pain and improving function and muscle strength when compared with the aerobic exercise regimen.